Study on the Time Domain Semi Analytical Method for Horizontal Vibration of Pile in Saturated Clay - Xin Ren; Li-an Wang (Applied Sciences, 2024)
Under the framework of Biot porous media theory, a fractional order Kelvin model is used to describe the rheological effects of soil skeletons, and a coupled vibration model of saturated clay and a pile foundation is constructed. The Laplace transform is used to derive the analytical solution of the control equation in the transformation domain, and then the time–domain solution is obtained through numerical inversion. By analyzing numerical examples, the displacement and internal force response of pile foundations under horizontal vibration loads, as well as the influence of parameters, are studied. The results show that the displacement and internal force response of pile foundation vibrations in saturated clay foundations have a delayed effect. The stronger the rheological properties of the foundation soil, the more obvious the delay, the lower the load frequency, and the more significant the influence of the rheological properties on the delayed effect. The stronger the rheological properties of the soil, the smaller the displacement amplitude of the pile foundation vibration, and the higher the load frequency, the greater the decrease in displacement amplitude. The stronger the rheological properties of the soil, the smaller the positive bending moment of the pile body, while the negative bending moment increases. Both positive and negative shear forces increase, but the shear force at the top of the pile is not affected. Therefore, when designing pile foundations in saturated clay foundations, it is necessary to appropriately increase the pile foundation or increase the reinforcement to meet the shear resistance of the pile foundation. The results of this study can provide a valuable reference for geotechnical and seismic engineers in pile foundation design.